Effects of Different Proportions of Amaranthus hypochondriacus Stem and Leaf Powder Inclusions on Growth Performance, Carcass Traits, and Blood Biochemical Parameters of Broilers - Ying Ren; Lingyu Liu; Shilong Zhou; Yantao Li; Yan Wang; Kang Yang; Wenxun Chen; Shengjun Zhao (Animals, 2023)
This experiment aimed to study the effects of different proportions of Amaranthus hypochondriacus stem and leaf powder (AHSL) on the growth performance, apparent nutrient digestibility, carcass traits, meat quality, and blood biochemical parameters of broilers from day 1 to day 42. The experiment utilized a single-factor experimental design, with a total of 216 one-day-old male broilers (Ross 308) randomly assigned to three dietary treatment groups (eight replicate cages of nine birds per cage). The dietary treatments included a control diet, a 3% AHSL diet and a 6% AHSL diet for days 0–21. Then, the 3% and 6% AHSL diets were changed to 5% and 10% AHSL for days 22–42. The results showed that the inclusion levels of AHSL did not affect growth performance, carcass traits, or meat quality on days 21 and 42 (p > 0.05). However, the inclusion levels of AHSL decreased the apparent nutrient digestibility (AND) of dry matter (DM) (p ˂ 0.001) and neutral detergent fiber (NDF) (p ˂ 0.001) and increased the serum concentration of phosphorus (p ˂ 0.001) on day 21. On day 42, the inclusion levels of AHSL decreased the AND of DM (p = 0.025) and NDF content (p ˂ 0.001), but increased the AND of crude protein (CP) (p = 0.004). In particular, the diet containing 10% AHSL significantly increased the serum enzyme activity of alkaline phosphatase (ALP) (p = 0.046) and the serum concentration of total protein (TP) (p ˂ 0.001) on day 42. Overall, AHSL can be used as a new and effective feed ingredient in broiler diets. It can replace part of the corn–soybean meal diet without any adverse effects, which is beneficial for conserving feed resources. Additionally, AHSL can be included at a level of up to 10% during the broiler growth period.